Judgment of infant cry: The roles of acoustic characteristics and sociodemographic characteristics1. (20th October 2014) - Esposito, Gianluca; Nakazawa, Jun; Venuti, Paola; Bornstein, Marc H.
Abstract Adult judgments of infant cry are determined by both acoustic properties of the cry and listener sociodemographic characteristics. The main purpose of this research was to investigate how these two sources shape adult judgments of infant cry. We systematically manipulated both the acoustic properties of infant cries and contrasted listener sociodemographic characteristics. Then, we asked participants to listen to several acoustic manipulations of infant cries and to judge the level of distress the infant was expressing and the level of distress participants felt when listening. Finally, as a contrasting condition, participants estimated the age of the crying infant. Using tree‐based models, we found that judgments of the level of distress the infant was expressing as well as the level of distress listeners felt are mainly accounted for by select acoustic properties of infant cry (proportion of sound/pause, fundamental frequency, and number of utterances), whereas age estimates of a crying infant are determined mainly by listener sociodemographic characteristics (gender and parental status). Implications for understanding infant cry and its effects as well as early caregiver‐infant interactions are discussed.